1990
DOI: 10.1063/1.457698
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of covalent clusters: Unimolecular decay of energized size-selected carbon cluster ions (C+n, 5≤n≤100)

Abstract: Controlling the internal energy content of sizeselected cluster ions: An experimental comparison of the metastable decay rate and photofragmentation methods of quantifying the internal excitation of (H2O)− n J. Chem. Phys. 95, 7998 (1991); 10.1063/1.461330 Reply to the Comment on: Evaporation of covalent clusters: Unimolecular decay of energized size selected carbon clusters J. Chem. Phys. 94, 6934 (1991); 10.1063/1.460227 Comment on: Evaporation of covalent clusters: Unimolecular decay of energized sizeselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…lc but this time the dominant fragmentation process is the loss of C~ with some contribution from single carbon atom loss. These results are in agreement with measurements of the photodissociation [13], collisionat dissociation [14] and metastable fragmentation [15] of small carbon cations where the dominant fragment was found to be C +_ 3 in each case.…”
Section: Photofragmentation Mass Spectra and Metastable Decaysupporting
confidence: 92%
See 1 more Smart Citation
“…lc but this time the dominant fragmentation process is the loss of C~ with some contribution from single carbon atom loss. These results are in agreement with measurements of the photodissociation [13], collisionat dissociation [14] and metastable fragmentation [15] of small carbon cations where the dominant fragment was found to be C +_ 3 in each case.…”
Section: Photofragmentation Mass Spectra and Metastable Decaysupporting
confidence: 92%
“…4, and the loss of a single carbon atom to give the particularly stable n --19, 15, 11 species. The trend observed for the small fragments is in very good agreement with the trend in the rate constants obtained for unimotecular decay of small carbon clusters [15] and with the experimentally determined binding energies [14,17]. In particular, C~3 has a particularly low binding energy due to its anti-aromatic character (4n rr electrons).…”
Section: Photofragmentation Mass Spectra and Metastable Decaysupporting
confidence: 84%
“…Geusic et al [30] and Radi et al [31,32] have shown that C3 loss is the predominant dissociation pathway for a majority of the small (n (30) carbon clusters, although C and C2 do originate from a small fraction of these clusters. However, C,4 -C60 were given as the only possible candidates for losing C4.…”
Section: Shown Inmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9] This is the correct approach for the very small clusters that behave like molecules and do not melt. However, it is now well established that even relatively small metal clusters can undergo a meltinglike transition with a significant latent heat.…”
Section: Introductionmentioning
confidence: 99%